Expert Perspectives on Competencies in Health Informatics for Informatics Students - Bhebe, Sophie; de La Harpe, Retha; Kaura, Doreen; Kabaso, Boniface (Journal of Health Informatics in Africa, 2024)
Background and Purpose: Informatics practitioners who are knowledgeable in health informatics and understand the need for clinical practitioner workflows contribute towards improved health information systems. The aim of this paper is to discuss insights gained from health informatics experts on their perspectives on competencies that could be taught to informatics students. The researcher explores (i) the competency needs of ICT students and practitioners to develop health ICTs with the involvement of healthcare practitioners, and (ii) how informatics education can be designed to incorporate healthcare domain knowledge in the training of ICT practitioners. Methods: A questionnaire was administered to health informatics experts. The research sample was purposively selected to include practitioners who have worked in the Health Informatics domain, and have at least a Master’s degree. Respondents identified topics and competencies appropriate for teaching undergraduate informatics students Results: Thematic analysis identified key competencies for different levels of study and design considerations for a Health Informatics course. Conclusions: Having Health domain Knowledge may provide opportunities for more roles that IT practitioners can play, especially for those who are not scientifically strong.